2017
DOI: 10.4236/fns.2017.85036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Sodium Thiocyanate and Sodium Percarbonate in the Activation of the Lactoperoxidase System in the Conservation of Raw Milk without Refrigeration in the Ecuadorian Tropics

Abstract: Milk production in Ecuador has enormous economic importance and large-, medium-and small-scale producers all participate in the market. There are multiple climatic regions, and dairy production is present in every one of them. High ambient temperatures in the Ecuadorian tropics represent a key challenge to the conservation of milk in the custody of smallholders. The objective of the present study was to evaluate the efficiency of the application of a chemical activator of the Lactoperoxidase System (LP-s) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The current findings are also in agreement with the findings of Nigusse and Seifu [29] (2007), who reported a decrease in TCC in cow milk after 7 h of activation of the LPS, as compared to the control treatment at ambient storage temperatures between 22 and 23 • C. The study by Campos-Vallejo et al [36] also reported 0.1, 0.56, 1.67, 2.66, and 1.8 log units of total coliform reduction at 0, 3, 6, 9, and 12 h of storage at ambient temperature, respectively. LPS activation affects the TCC of cow milk, confirming its ability to preserve milk quality and the combination of bactericidal and bacteriostatic effects on mesophilic bacteria, including coliforms [37].…”
Section: Effect Of Lpss On the Microbiological Quality Of Collector's...supporting
confidence: 93%
“…The current findings are also in agreement with the findings of Nigusse and Seifu [29] (2007), who reported a decrease in TCC in cow milk after 7 h of activation of the LPS, as compared to the control treatment at ambient storage temperatures between 22 and 23 • C. The study by Campos-Vallejo et al [36] also reported 0.1, 0.56, 1.67, 2.66, and 1.8 log units of total coliform reduction at 0, 3, 6, 9, and 12 h of storage at ambient temperature, respectively. LPS activation affects the TCC of cow milk, confirming its ability to preserve milk quality and the combination of bactericidal and bacteriostatic effects on mesophilic bacteria, including coliforms [37].…”
Section: Effect Of Lpss On the Microbiological Quality Of Collector's...supporting
confidence: 93%
“…The current finding was also in agreement with the finding of Nigusse and Seifu (2007), who reported a decrease in TCC in cow milk after 7 hours of activation of LPS as compared to the control treatment at ambient storage temperatures between 22 and 23 °C. The study by Campos-Vallejo et al (2017) also reported 0.1, 0.56, 1.67, 2.66, and 1.8 log units of total coliform reduction at 0, 3, 6, 9, and 12 hours of storage at ambient temperature, respectively. LPS activation affects the TCC of cow milk, confirming the ability to preserve milk quality and the combination of bactericidal and bacteriostatic effects on mesophilic bacteria, including coliforms .…”
Section: Effect Of Lps On Microbiological Quality Of Collector's Milkmentioning
confidence: 83%
“…Regarding the presence of hydrogen peroxide (which is not allowed by Ecuadorian legislation), there is wide variability among the studies; for example, in the research of [ 31 , 32 , 82 ], its levels are farthest from the zero point or the line of incidence, so they disagree with the majority of studies ( Figure 19 ). In Ecuador, the use of hydrogen peroxide is prohibited because it is used to mask the acidity of milk [ 111 , 112 ]; however, there are studies that indicate the benefits of using it to preserve milk for up to 8 h at room temperature without losing its organoleptic characteristics, even in the Ecuadorian tropics, where ambient temperatures can be above 25 °C [ 113 ].…”
Section: Resultsmentioning
confidence: 99%